(untitled) (Revista de Medicina Clinica, 2021)
In relation to the current SARS-CoV-2 pandemic, cases of Platypnea Orthodeoxy Syndrome (SPO) have been documented, the symptoms of which have become apparent once the acute infection by COVID-19 has passed. This syndrome is characterized by positional dyspnea accompanied by significant arterial desaturation to adopt when adopting a standing position, with symptoms remitting when returning to decubitus position. Its pathophysiology is still a mystery, although the most documented cause is cardiac - due to the existence of a patent foramen ovale (PFO) -. We present the case of a patient from our hospital who, after passing the SARS-CoV-2 infection, debuted with SPO and in which the timely diagnosis will improve the cause and restore the patient’s previous quality of life.